Intergrated transport application / Muhammad Aizuddin Mohd Alias, Ahmad Dzulkifli and Sharul Aiman Mohammed Samsudin - Mohd Alias, Muhammad Aizuddin; Dzulkifli, Ahmad; Mohammed Samsudin, Sharul Aiman (2017)
After initial observation towards the public transportation, the team had chosen an application that we believe can ease the movement of people. Nowadays people especially student and worker at Kuala Lumpur and Selangor need public transport which is most of them more emphasize about the time and the quality of public transportation. Nowadays, Selangor and Wilayah Persekutuan Kuala Lumpur implement the new development which is Transit Oriented Development (TOD) .the people and resident that live in TOD area need public transportation as their mode of transportation. Our application offer smart integrated public transportation that can ease and make the user journey more convenience.